Phototunable surface interactions - Erath, Johann; Cui, Jiaxi; Schmid, Jasmin; Kappl, Michael; Del Campo, Aranzazu; Fery, Andreas (Langmuir, 2013)
Photoresponsive polymer brushes constitute an attractive platform for tuning surface properties and functionality. Since the degree of photoconversion can be controlled by the light dose, functional states with intermediate properties between those of the nonexposed and fully exposed brushes are accessible. Here we investigate the light-modulated interfacial, adhesion, and frictional properties of photosensitive polymer brushes with a methacrylate backbone and ionizable -COOH side groups modified with the photoremovable group 6-nitroveratryloxycarbonyl (NVOC). The original brush (PNVOCMA) gradually changes into a charged poly(methacrylic acid) (PMAA) brush upon exposure to ultraviolet light due to the photoremoval of the chromophore and generation of free COOH groups. We show how the physical properties of the brush can be gradually tuned with the exposure dose using condensation microscopy, atomic force microscopy (AFM), force mapping, and friction force spectroscopy. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20